The role of vanilloid receptor type 1 (TRPV1) in hyperalgesia related to bovine digital dermatitis - Bonacin, Yuri S. [UNESP]; Marques, Isabela C.S.; Garcia, Sérgio B.; Silva, Samara B.G. [UNESP]; Canola, Paulo A. [UNESP]; Marques, José A. [UNESP] (American Dairy Science Association, 2020)
Bovine digital dermatitis is a contagious and chronic disease affecting the digits of dairy cattle worldwide. Tissue degradation may alter ionic channels and further activate vanilloid channels, more specifically the vanilloid receptor type 1 (TRPV1) that can generate and modulate hyperalgesia in cows affected with bovine digital dermatitis. The aim of this pilot study was to identify and quantify TRPV1 channels in dairy cows presenting with different stages of bovine digital dermatitis and compare these data according to the disease evolution and degree of hyperalgesia described in previous studies. Biopsies were taken from 15 lactating Holstein cows (23 lesions), and immunochemistry was performed to identify the number of TRPV1 fibers in the 4 M-stages of digital dermatitis and the control group. This pilot study had 5 experimental groups, M1 (5 samples), M2 (5 samples), M3 (4 samples), M4 (4 samples), and the control group (5 samples), with inclusion criteria was the presence of a bovine digital dermatitis lesion in at least one digit. The pilot results demonstrate an increase in expression of TRPV1 receptors in group M4 in comparison with the other groups. Bovine digital dermatitis may cause an increase in expression of TRPV1 receptors in the chronic stages of the disease, possibly contributing to the hyperalgesia described in affected animals; nevertheless, further research is needed to define this relation.
Keywords: capsaicin; chronic; hoof; lameness; pain